SCIENTIFIC ASTRONOMICAL SCHOOL BY PROFESSOR VOLODYMYR P. TSESEVICH ON THE PHYSICS OF VARIABLE STARS - Vavilova, I. B. (Одеські астрономічні публікації, 2017)
This paper is dedicated to the Prof. Volodymyr Platonovych Tsesevich (1907–1983), an outstanding scientist and legendary personality of the XX century. We describe briefly the Kyiv period of his life and activity taken from his Personal Dossier from the Archive of the Presidium of the NAS of Ukraine. A particular attention is paid to the role by V.P. Tsesevich in the development of astrophysical research at the Main Astronomical Observatory of the Academy of Sciences of UkrSSR, when he served as the Director (19.11.1948–03.05.1951), and to the fruitful cooperation between Kyiv and Odesa astronomers. We present briefly a “tree” of the scientific astronomical school by Prof. V.P. Tsesevich on the physics of stars. The data were obtained from different archives (Astronomical Observatory of the I.I. Mechnikov National University of Odesa, Main Astronomical Observatory of the NAS of Ukraine, Archive of the Vernadsky National Library, Archive of the Russian AS, and other institutions). The full database contains of a brief information on the about 100 representatives of this school as follows: name, title and year of thesis’s defense, past/present affiliation). The scientific school is formed since 1950-ies till now having its greatest continuation in the work of such astronomers as N.S.Komarov, V.G.Karetnikov, Yu.S. Romanov, and I.L.Andronov (a branch of this school after V.P. Tsesevich), as well as S.M.Andrievsky as the follower by V.G. Karetnikov and T.V. Mishenina, V.F. Gopka, V.V. Kovtykh as the followers by N.S. Komarov. The given information on the school by V.P. Tsesevich is not absolutely full, for example, 1) there are no the data on thesis’s defense under his supervision before 1948; 2) information on the astronomical school developed by A.M. Stafeev and some other scientists is a very poor; 3) some inaccuracies may be present. We will grateful for all the additions and corrections to update a tree of this scientific school, which played and plays a prominent role in the development of our knowledge on physics of stars.